Research on sapphire micro-blind-hole machining based on femtosecond laser. (26th July 2020) - Fang, Xuyang; Dou, Jian; Dong, Xiangyang; Duan, Wenqiang
Abstract: The experiment of micro-blind-hole processing of sapphire by a femtosecond pulsed laser with a wavelength of 1030 nm, repetition frequency of 100 kHz and pulse width of 290 fs was carried out to study the effects of laser power, scanning speed, repeated scanning times and defocusing amount on the morphology of micro-blind holes. It can be seen from the experimental results that the depth of the micro-blind-hole increases as the laser power increases, the scanning speed decreases, and the repeated scanning times increase. When the defocusing amount is positive, the depth of micro-blind-hole decreases with the increase of defocusing amount. The depth is constant due to the filament effect during negative defocusing amount. The size of the micro-blind hole is mainly decided by the path of the circumferential cutting process. It is indicated that fine micromachining of sapphire materials can be achieved by controlling femtosecond laser parameters and processing parameters.